2014
DOI: 10.5424/sjar/2014124-5929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat cultivar, metabolizable energy level, and xylanase supplementation to laying hens diet on performance, egg quality traits, and selected blood parameters

Abstract: A 2 x 2 x 2 factorial arrangement of treatments was conducted to evaluate the effects of two dietary apparent metabolizable energy (AME) levels (2,720 and 2,580 kcal kg-1 diet) and enzyme (0 and 0.3 g kg-1 diet, Grindazym® GP 15,000 with mostly xylanase activity) supplementation on the performance of laying hens fed diets based on two wheat cultivars (Marvdasht and Sardari). Experimental diets were formulated to have a constant energy to protein ratio and were fed to 65-wk-old Lohmann LSL-Lite laying hens for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…In contrast, Mirzaee et al (2014) observed no significant impact of supplemental enzyme on eggshell weight and shell thickness in laying hens fed with wheat-included diets. Moreover, Lázaro et al (2003) showed no significant effect of supplemental enzyme on the shell weight in laying hens fed with diets based on rye, wheat and barley.…”
Section: Egg Quality Traitsmentioning
confidence: 58%
“…In contrast, Mirzaee et al (2014) observed no significant impact of supplemental enzyme on eggshell weight and shell thickness in laying hens fed with wheat-included diets. Moreover, Lázaro et al (2003) showed no significant effect of supplemental enzyme on the shell weight in laying hens fed with diets based on rye, wheat and barley.…”
Section: Egg Quality Traitsmentioning
confidence: 58%
“…This response can be explained by the higher daily ME intake. Birds are known to consume a certain amount of feed to meet primarily their energy requirement (Bertechini, 2013), and variations in the dietary energy level prompt changes in feed intake, thus influencing the intake of all nutrients (Mirzaee, Torki, & Habibian, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidative, protective against reactive oxygen species, functions of inositol 1,2,3-triphosphate and inositol 1,2,3,6-tetrakisphosphate are well documented (Phillippy & Graf, 1997). Using an enzyme preparation with mostly xylanase activity, Mirzaee et al (2014) reported no change in differential count of white blood cells in 71-week-old Lohmann LSL-Lite laying hens. However, it is not clear why the simultaneous use of phytase and xylanase reduced the percentage of lymphocytes, and as a result produced the highest H/L ratio.…”
Section: Discussionmentioning
confidence: 99%